Analysis of Settlements along Abandoned Railway Tracks in Majalaya Subdistrict, Bandung Regency, Indonesia - Septi Sri Rahmawati; Sudrajat Sudrajat; Sri Rum Giyarsih (Universitas Muhammadiyah Surakarta, 2020)
Settlements in urban areas expand as the population grows and are influenced by growth centres. This research was designed to identify the quality of informal settlements along abandoned railwaytracks in the Majalaya District, an industrial centre in Bandung Regency, Jawa Barat Province, Indonesia. A quantitative method was employed, with proportional random sampling and the use of both primary and secondary data. The primary data referred to the conditions of the slum areas, while the secondary data were images, Regional Spatial Planning (RTRW) documents and RTRW maps. The quantitative analysis employed scoring through slum settlement assessment indicators, while spatial analysis was supported by regional data. The results from the research show that although housing construction quality varies, most settlements are illegal and prone to flooding, fire, and contagious diseases. The research should be beneficial for the government in promoting and implementing slum eradication programmes in urban areas.